Effect of Insoluble Okara Fiber on the Properties of Okara Protein Emulsion - Zhongjiang WANG; Yanan GUO; Shuangqi LIU; Bailiang LI; Zhen ZHANG; Jun LIU; Zhen FENG; Zengwang GUO (Shipin gongye ke-ji, 2023)
This article explored the effect of insoluble okara fiber (IOF) on the properties of okara protein (SOP) emulsion. The effects of different concentrations of IOF (0.25 wt%, 0.50 wt%, 0.75 wt% and 1.00 wt%) on the microstructure, interfacial activity, emulsifying activity and stability of SOP emulsion were studied with sunflower oil as oil phase. The results showed that with the increase of the IOF concentration, the particle size of the SOP/IOF emulsion showed a trend of gradual increase. The laser confocal microscope observation experiment showed that the emulsion droplets change in the same trend, and the absolute value of the zeta potential presents an increasing trend. The content and concentration of interfacial protein showed an increasing trend, and the change of rheological index showed that the trend of shear thinning was increasing, and high concentration of IOF could significantly enhance the long-term storage stability, acid resistance stability and salt resistance stability of SOP emulsion. This provides a theoretical basis for the further application of IOF in the protein emulsion gel system.